Interfacial Phenomena on Biological Membranes - Arakha, Manoranjan; Jha, Suman (Series in BioEngineering, 2018)
This book focuses on important interfacial phenomena, such as interfacial potential and interfacial multi-functionality, responsible for determining the fate of nanoparticles inside the biological milieu. Additionally, this book explores the role of surface defects in photocatalytic nanoparticles in defining the nanoparticle interaction to biological membrane and cytotoxic propensity.The authors describe the interfacial assembly of peptide/protein on conformational/functional dynamics of the peptide/protein, which may be adopted as an approach to moderate the protein misfolding diseases.